Zno Micro/Nanostructures Grown on Sapphire Substrates Using Low-Temperature Vapor-Trapped Thermal Chemical Vapor Deposition: Structural and Optical Properties - Hu, Po-Sheng (Materials (Basel), 2017)
In this research, the Zn(C(5)H(7)O(2))(2)·xH(2)O-based growth of ZnO micro/nanostructures in a low temperature, vapor-trapped chemical vapor deposition system was attempted to optimize structural and optical properties for potential biomedical applications. By trapping in-flow gas molecules and Zinc vapor inside a chamber tube by partially obstructing a chamber outlet, a high pressure condition can be achieved, and this experimental setup has the advantages of ease of synthesis, being a low temperature process, and cost effectiveness. Empirically, the growth process proceeded under a chamber condition of an atmospheric pressure of 730 torr, a controlled volume flow rate of input gas, N(2)/O(2), of 500/500 Standard Cubic Centimeters per Minute (SCCM), and a designated oven temperature of 500 °C. Specifically, the dependence of structural and optical properties of the structures on growth duration and spatially dependent temperature were investigated utilizing scanning electron microscopy, X-ray diffraction (XRD), photoluminescence (PL), and ultraviolet-visible transmission spectroscopy. The experimental results indicate that the grown thin film observed with hexagonal structures and higher structural uniformity enables more prominent structural and optical signatures. XRD spectra present the dominant peaks along crystal planes of (002) and (101) as the main direction of crystallization. In addition, while the structures excited with laser wavelength of 325 nm emit a signature radiation around 380 nm, an ultraviolet lamp with a wavelength of 254 nm revealed distinctive photoluminescence peaks at 363.96 nm and 403.52 nm, elucidating different degrees of structural correlation as functions of growth duration and the spatial gradient of temperature. Transmittance spectra of the structures illustrate typical variation in the wavelength range of 200 nm to 400 nm, and its structural correlation is less significant when compared with PL.